Dynamics of a three‐dimensional systems of rational difference equations. (16th June 2015) - Elsayed, E. M.; Ahmed, A. M.
Abstract : We investigate in this paper the solutions and the periodicity of the following rational systems of difference equations of three‐dimensional x n + 1 = y n x n − 2 x n − 2 ± z n − 1, y n + 1 = z n y n − 2 y n − 2 ± x n − 1, z n + 1 = x n z n − 2 z n − 2 ± y n − 1, with initial conditions x −2, x −1, x 0, y −2, y −1, y 0, z −2, z −1 and z 0 are nonzero real numbers. Copyright © 2015 John Wiley & Sons, Ltd.